Debating Resource-Driven Development: A Comparative Analysis of Media Coverage on the Pacific Northwest LNG Project in British Columbia - Chen, Sibo (Frontiers in Communication, 2020)
In Canada, the provincial government of British Columbia has been keen on building an export-oriented liquefied natural gas (LNG) industry since 2011. This paper examines media coverage of the Pacific NorthWest LNG project (PNW), which was considered as the flagship proposal of the BC LNG initiative, until its abrupt cancellation in July 2017. By tracing how six Canadian media outlets reported the rise and fall of PNW over a 36-month period, the paper explicates the intricate political and ideological struggles underlying the Canadian political economy’s growing dependence upon unconventional fossil fuels. The comparative analysis reveals that when explaining the project’s cancellation, fossil fuel advocates repeatedly deployed the “jobs killed by environmentalists” argument via opinion pieces appearing in commercial newspapers. This diagnosis, however, downplayed the far-reaching impacts of Asia’s LNG market conditions prior to the cancellation. By comparison, independent media played an important role in assisting LNG opponents to communicate PNW’s fragile economic basis to a wide audience. Overall, these findings highlight the significance of independent media in supporting diverse news accounts of energy controversies.